2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32035
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Mixed-Mode Instructional Delivery to Thrive within STEM Curricula

Abstract: Florida (UCF), where he has been a full-time faculty member since 1993. His educational research interests focus on classroom instructional technologies and the digitization of STEM assessments. He is Principal Investigator of the NSF Workshop on Digitally-Mediated Team Learning and the organizer of faculty development workshops on Assessment Digitization Innovation and also on Virtualized Active Learning. He has completed over 275 technical and educational publications, 47 funded projects as PI/Co-I, and 22 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…As reported in literature, the positive outcomes of technology-reinforced learning in STEM education include positive attitudes toward content learning, greater retention of direct content and greater transfer to other areas [1]- [4]. "Blended-learning," "flipped-classroom," "hybrid-learning," and "mixedmode" are some examples of the newer pedagogical models implemented in recent years by educational researchers [5]- [8]. Although each of these pedagogical approaches have multiple definitions and have been implemented in diverse ways by researchers, the overarching theme in all these models is incorporation of online or electronic instruction beyond simple in-class lectures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in literature, the positive outcomes of technology-reinforced learning in STEM education include positive attitudes toward content learning, greater retention of direct content and greater transfer to other areas [1]- [4]. "Blended-learning," "flipped-classroom," "hybrid-learning," and "mixedmode" are some examples of the newer pedagogical models implemented in recent years by educational researchers [5]- [8]. Although each of these pedagogical approaches have multiple definitions and have been implemented in diverse ways by researchers, the overarching theme in all these models is incorporation of online or electronic instruction beyond simple in-class lectures.…”
Section: Introductionmentioning
confidence: 99%
“…A growing trend in the approaches used in the implementation of blended learning is the blended approach that combines face-to-face and online instruction while reducing in-class lecture time [11]. In this model, online instruction is mediated through lecture videos while lecture time is devoted to additional classroom-based instructional activities [8]. Blended approach also encompasses the flipped-classroom pedagogy, an approach that inverts events traditionally occurring inside the classroom to outside of the classroom and vice-versa [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Both our in-person and online courses will be focusing on improving our exam methodology going forward, emphasizing auto-generated auto-graded exams, hoping to model the successes at University of Illinois [12], [13] and University of Central Florida [14], [15], [16].…”
Section: -2019mentioning
confidence: 99%
“…A blended approach combines face-to-face and online instruction while reducing in-class lecture time [3]. In this model, online instruction is mediated through lecture videos while lecture time is devoted to problem-solving activities [4]. The blended approach also encompasses the flipped-classroom pedagogy, an approach that inverts instruction traditionally occurring inside the classroom to online [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the implementation of a blended engineering master's program in Spain not only increased enrollment, but also resulted in increased students' satisfaction, interaction with instructors, and learning performance [8]. The blended approach has been utilized in large-size engineering classes and the results have shown that students were more satisfied and that they believe they had more opportunities to apply their knowledge [2], [4]. Similarly, when the blended approach was used in a biology class, the findings showed that students learned deeper and their grades were better than those learning in the traditional classroom [9].…”
Section: Introductionmentioning
confidence: 99%